Optimization of Islamic Bank Profitability: Overview of Capital, Liquidity, Operational Efficiency and Problem Financing - Afri Cahyani, Ikah; Tubastuvi, Naelati (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
This research aims to look at the influence of capital, liquidity, operational efficiency and problematic financing on profitability. The sample selection used a purposive sampling method where the sample size was obtained from 13 sharia banks in Indonesia during the 2018-2022 period, by analyzing quarterly sharia banking financial reports. The analysis used in this research is multiple linear regression analysis using SPSS 25. The result show that partially operating expenses operating income (BOPO) have a negative and significant effect on return on asset (ROA), where Islamic banking needs to increase efficiency or reduse operational costs to increase profitability. then Capital Adequacy Ratio (CAR), financing to deposit ratio (FDR), and non performing financing (NPF) do not have a significant effect on ROA. It can be concluded that operational efficiency has an effect on profitability while capital, liquidity, and problematic financing have no effect on profitability.